2018
DOI: 10.1111/cogs.12607
|View full text |Cite
|
Sign up to set email alerts
|

Due Process in Dual Process: Model‐Recovery Simulations of Decision‐Bound Strategy Analysis in Category Learning

Abstract: Behavioral evidence for the COVIS dual-process model of category learning has been widely reported in over a hundred publications (Ashby & Valentin, ). It is generally accepted that the validity of such evidence depends on the accurate identification of individual participants' categorization strategies, a task that usually falls to Decision Bound analysis (Maddox & Ashby, ). Here, we examine the accuracy of this analysis in a series of model-recovery simulations. In Simulation 1, over a third of simulated par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 68 publications
(291 reference statements)
2
18
0
Order By: Relevance
“…Ashby et al, 1998;Kemler Nelson, 1984;Smith & Shapiro, 1989;Ward, 1983), it is fully consistent with a substantial body of more recent work, across several different procedures. For example, it is consistent with results from the match-to-standards procedure Milton & Wills, 2004;Milton et al, 2009;Wills et al, 2013), the triad procedure (Wills et al, 2015), the criterial-attribute procedure (Wills et al, 2015), and information-integration category learning procedure (Carpenter et al, 2016;Edmunds et al, 2015Edmunds et al, , 2018Edmunds et al, , 2019Newell et al, 2013). It finds support from not only human behavioral data, but also from comparative work with rats and pigeons (Lea et al, 2018(Lea et al, , 2006Wills et al, 2009) and from functional imaging data in humans (Carpenter et al, 2016;Milton et al, 2009).…”
Section: Discussionsupporting
confidence: 75%
“…Ashby et al, 1998;Kemler Nelson, 1984;Smith & Shapiro, 1989;Ward, 1983), it is fully consistent with a substantial body of more recent work, across several different procedures. For example, it is consistent with results from the match-to-standards procedure Milton & Wills, 2004;Milton et al, 2009;Wills et al, 2013), the triad procedure (Wills et al, 2015), the criterial-attribute procedure (Wills et al, 2015), and information-integration category learning procedure (Carpenter et al, 2016;Edmunds et al, 2015Edmunds et al, , 2018Edmunds et al, , 2019Newell et al, 2013). It finds support from not only human behavioral data, but also from comparative work with rats and pigeons (Lea et al, 2018(Lea et al, , 2006Wills et al, 2009) and from functional imaging data in humans (Carpenter et al, 2016;Milton et al, 2009).…”
Section: Discussionsupporting
confidence: 75%
“…Ashby, Queller, & Berretty, 1999;Milton, Longmore, & Wills, 2008;Wills, Inkster, & Milton, 2015). Further, using a unidimensional rule in II tasks results in performance around 75%, well above chance (Edmunds, Milton, & Wills, 2018). To test this possibility we added control conditions (one for each category task), where participants had to complete the final transfer test without prior categorization training.…”
Section: The Current Workmentioning
confidence: 99%
“…Note that in previous experiments using these types of category structures, researchers have used a model-based decision-bound analysis informed by signal detection theory (Ashby & Gott, 1988;. However, recent work has shown that this analysis can be unreliable and consequently hard to interpret (Donkin, Newell, Kalish, Dunn, & Nosofsky, 2015;Edmunds et al, 2018). Therefore, we have not included this analysis in the main text, although it is available in the Appendix for those interested.…”
Section: The Questionnairementioning
confidence: 99%
“…One might see such a claim as supported by the fact that the strategies people verbalize in this task are poorly related to the strategies indicated by standard decision-bound computational modeling of their categorization responses (Edmunds et al, 2015(Edmunds et al, , 2019. However, this decision-bound modeling is flawed (Edmunds et al, 2018). The flaw is sufficiently fundamental that the results reported in Smith et al (2014b)-a key paper in Smith and Church's reviewcan be modeled under the assumption that all participants in the information-integration task use easily verbalizable multidimensional rules (Edmunds et al, 2018), see also Donkin et al (2015) for a related conclusion.…”
Section: The Information-integration Category-learning Taskmentioning
confidence: 99%
“…However, this decision-bound modeling is flawed (Edmunds et al, 2018). The flaw is sufficiently fundamental that the results reported in Smith et al (2014b)-a key paper in Smith and Church's reviewcan be modeled under the assumption that all participants in the information-integration task use easily verbalizable multidimensional rules (Edmunds et al, 2018), see also Donkin et al (2015) for a related conclusion.…”
Section: The Information-integration Category-learning Taskmentioning
confidence: 99%